The Transformation of Islamic Boarding School Education in the Digital Era: Opportunities, Challenges, and Strategies for Preserving the Pesantren Identity (A Literature Review) - Ahmad Nur Qurbani; Ari Afwan Hidayat Azuzzurrizqi (Classroom: Journal of Islamic Education, 2026)
The rapid development of digital technology has significantly transformed educational systems worldwide, including Islamic boarding schools (pesantren). As one of Indonesia’s oldest Islamic educational institutions, pesantren are required to adapt to technological advancements while preserving their distinctive educational values and identity. This study aims to analyze the opportunities and challenges of digital transformation in pesantren education and to formulate strategies for maintaining pesantren identity in the digital era. This research employs a qualitative approach using a library research method. Data were collected from scientific journals, books, government regulations, and relevant academic publications discussing digital transformation, Islamic education, and pesantren development. The findings reveal that digital transformation provides substantial opportunities for pesantren, including wider access to learning resources, innovation in educational methods, strengthening digital da'wah, and improving institutional management. However, several challenges emerge, such as digital literacy disparities, weakening traditional teacher-student relationships, erosion of pesantren values, and disruption of religious authority due to unrestricted access to online information. To address these challenges, pesantren need to implement adaptive and integrative strategies through strengthening Islamic character education, developing Islamic digital literacy, integrating technology into learning while maintaining traditional values, enhancing the role of kiai as educational leaders, and implementing hybrid curricula that combine classical Islamic sciences with digital competencies. This study concludes that digital transformation and the preservation of pesantren identity are not contradictory goals but can be harmonized through value-based educational innovation.